Salud y bienestar en el tiempo de la pandemia del COVID-19 - Hernández Garnica, Clotilde; Suárez-Lugo, Nery de la Concepcion (Horizonte Sanitario, 2021)
Abstract Objective. To describe people’s perceptions and expectations about their health and well-being, during and after the quarantine by COVID-19 in Latin America and to identify the changes that will be required to face the new reality.Material and method. Online survey aimed at the population over 18 years of age with a questionnaire on daily activities (coexistence, health, well-being and shopping) during quarantine and expectations about their health, well-being and daily life after quarantine. A non-probability sampling was carried out in 18 countries, obtaining a sample of 1066 interviewees.Results. For the population- For the people, fear to get sick was the most difficult; the health authority is the source of most credibility and the social network, the least. They consider it is important to stop the deterioration of their health, since before suffering the effects of SARS-CoV-2, other ills were allowed to grow such as: eating disorders (overweight), diabetes, Hypertension, addictions (smoking, alcoholism, drug addiction) or stress due to working conditions. However, the population perceives that they can acquire healthy habits, that their well-being depends on themselves and that they can make changes at least in the family, to improve their physical and mental condition and stay healthy.Conclusions. The perceptions of the surveyed population about their health and well-being during and after the COVID-19 quarantine and about changes that will be required in the new reality, are indicative of value to draw strategies, with a social marketing approach, that have an impact positively in the behaviors that need to be achievedKeywords: COVID-19, perception of health, well-being, daily activities.